2020
DOI: 10.1177/2631831820972859
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Intimacy and Sexuality in Persons With Dementia

Abstract: Sexuality in dementia is infrequently addressed. Dementia is characterized by a progressive deterioration in all domains of functioning, including loss of sexual function. However, the diagnosis of dementia does not mean an immediate or complete cessation of sexuality in the person, or a loss of the ability to consent to sexual activity with a partner. A discussion of sexuality in dementia occurs infrequently in clinical care for several reasons. These include (a) a discomfort in discussing sexuality in older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The intimate sexual activities of people with dementia have often been referred to in the literature as “inappropriate,” “improper,” and “hypersexual” (Benbow & Beeston, 2012). Studies highlight the difficulty of destigmatizing sexuality when considering couples affected by dementia, and the difficulty to understand and place sexual intimacy as a changing need throughout an individual’s lifespan, irrespective of a dementia diagnosis (Bartlett & O’Connor, 2010; D’cruz, Andrade, & Rao, 2020; Sandberg, 2020). As a result, this construction of sexual intimacy as pathological ignores the complexity of the feelings of couples living with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The intimate sexual activities of people with dementia have often been referred to in the literature as “inappropriate,” “improper,” and “hypersexual” (Benbow & Beeston, 2012). Studies highlight the difficulty of destigmatizing sexuality when considering couples affected by dementia, and the difficulty to understand and place sexual intimacy as a changing need throughout an individual’s lifespan, irrespective of a dementia diagnosis (Bartlett & O’Connor, 2010; D’cruz, Andrade, & Rao, 2020; Sandberg, 2020). As a result, this construction of sexual intimacy as pathological ignores the complexity of the feelings of couples living with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The literature regarding sexuality in people with dementia is sparse for various reasons such as discomfort in discussing issues of sexuality with this population, fear of adverse sociocultural implications, and unscientific assumption of the end of sexual life with the onset of dementia. 50 Studies have shown that up to 50% of the patients with Alzheimer’s disease have one or the other sexual dysfunction, majority of which is erectile dysfunction which is independent of age, cognitive decline, physical illness, or medications. 51 The English Longitudinal Study of Aging, which was conducted on persons with dementia with an age group of 50 to 90 years living in the community, has reported that those with milder dementia severity and better physical activity levels were more sexually active.…”
Section: Sexuality In Persons With Dementiamentioning
confidence: 99%
“… 57 Sexual abuse in dementia needs to be managed by a multidisciplinary team with appropriate safety measures and legal assistance. 50 …”
Section: Sexuality In Persons With Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses need to adopt a supportive approach when dealing with these highly sensitive situations (Thys et al, 2019). There is a tension between ensuring the autonomy of the person with dementia and their right to express their sexuality, and protecting family and other residents from harm (Wiskerke & Manthorp, 2019; D’cruz et al., 2020). Issues related to sexuality combined with consent and ethical demarcation can be complicated to handle and put a heavy burden on nursing staff and relatives (Mahieu et al., 2014).…”
Section: Introductionmentioning
confidence: 99%